Agroecology Education by Bicycle on Two Continents: Student Perceptions and Instructor Reflections. Issue 1 (18th December 2015) - Porter, Paul M.; Runck, Bryan C.; Brakke, Mary P.; Wagner, Margaret
Abstract : Given that much of the learning about international agroecology would ideally occur outside the classroom, adventure learning (AL) and systems action education (SAE) can offer synergistic approaches that synthesize these methodologies into a cohesive student learning experience. This article reports on the evolution of a series of international agroecology courses offered from 2009 to 2011 that progressively integrated AL and SAE approaches in course design. The courses were taught by a University of Minnesota professor as he bicycled across Africa (2009 and 2010) and South America (2011), exploring various landscapes, crops, climatic regions, and food systems with students back home via distance technologies. End‐of‐course survey responses indicated that students (1) did not find the course any more rigorous than similar level courses, (2) found the course much more unique ( p < 0.01), and (3) increased their desire to travel abroad ( p < 0.01). Our examination also revealed challenges and opportunities inherent with AL and SAE–merged classrooms. Overall, we found that AL and SAE approaches could be integrated to enhance agroecology education and can make courses inspiring, challenging, and rewarding. The result could have implications for schools that seek to prepare students to work in a global environment.